Probe for detecting HBV-DNA and application and method thereof
By designing special padlock probe DNA and using a zeolite imidazole acid frame structure wrapped in methylene blue, as well as a composite material modified electrode of MXene and multi-walled carbon nanotubes, the problems of low signal-to-noise ratio and limited detection sensitivity in the prior art are solved, and high sensitivity and specific HBV-DNA detection are achieved.
Patent Information
- Application Number
- CN202411640726.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has low signal-to-noise ratio when detecting HBV-DNA, resulting in limited detection sensitivity, and traditional rolling ring amplification designs may undergo nonspecific cyclization and intermolecular cross-reactions.
A special padlock probe DNA was designed, and the remaining base sequences treated with exonuclease III were amplified as RCA templates to release pyrophosphate as signal amplification. At the same time, the zeolite imidazole acid frame structure wrapped in methylene blue was used to detect the by-product of RCA amplification, releasing a large amount of methylene blue as a signal again. Signal recognition and amplification are performed using electrodes modified with composite materials of MXene and multi-walled carbon nanotubes.
High sensitivity detection of HBV-DNA is achieved, with a detection range of 1.0~1.0×106pM, a detection limit of 50.3fM, and has good specificity and recovery rate in actual serum samples.
Smart Images

Figure CN119506476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical detection technology, and more specifically, to a probe for detecting HBV-DNA and its application and method. Background Art
[0002] Hepatitis B virus (HBV) infection is the main cause of cirrhosis and liver cancer. HBV-DNA is an important marker for detecting hepatitis B virus and can provide a basis for diagnosing HBV infection.
[0003] The MB-encapsulated zeolite imidazolate framework (MB@ZIF-90) is a new ideal composite material for detecting the amplification byproduct pyrophosphate in DNA amplification procedures due to its specific structural collapse effect on pyrophosphate and phosphate. However, its response to dATP also limits its application in DNA amplification procedures.
[0004] Due to the advantages of padlock-assisted rolling circle amplification (RCA) such as high efficiency of isothermal amplification, convenient editing, and flexible signal output, a large number of studies have achieved effective application in nucleic acid detection. However, in the process of target recognition, the traditional rolling circle amplification design only relies on base complementary pairing and the fidelity of the ligase used to ensure specificity, and nonspecific cyclization and intermolecular cross-reactions may occur, which greatly reduces the signal-to-noise ratio (SNR) and limits the detection sensitivity.
[0005] MXene is a new type of two-dimensional (2D) graphene-like multilayer nanomaterial, Ti3C2T x MXene (hereafter referred to as MXene) is a layered structure with unique metallic conductivity, high specific surface area, ultra-large interlayer spacing, and abundant functional groups. At the same time, electrostatic attraction and abundant functional groups (-O, -OH and -F) are conducive to the adsorption of cationic dyes such as methylene blue (MB) by MXene. These attractive advantages have promoted the development of MXene in the fields of sensors, supercapacitors, and electrocatalytic water decomposition. However, due to the strong van der Waals forces between adjacent layers, MXene easily forms tightly packed sheets, which hinders the practical application of MXene. Multi-walled carbon nanotubes (MWCNTs) are typical sp 2 -Hybrid carbon materials have the characteristics of easy functionalization, excellent electrochemical catalytic performance and good electron transfer ability, and can be used as good additives for MXene interlayers. However, the composite materials combined with MXene and multi-walled carbon nanotubes (MWCNTs) are mostly used in the field of dye adsorption and degradation due to their negative charge characteristics, but few people use this property in electrochemical sensors. Summary of the invention
[0006] The purpose of the present invention is to provide a special padlock probe DNA as a recognition probe for HBV-DNA. The remaining base sequence after treatment with exonuclease III is used as an RCA template for amplification to release the amplification product pyrophosphate (PPi), thereby forming a signal amplification effect. The zeolite imidazole acid framework structure (MB@ZIF-90) encapsulated with methylene blue (MB) plays the role of detecting the RCA amplification byproduct PPi, releasing a large amount of MB as a second amplification of the signal. The electrode modified with the MX / MWCNTs composite material composed of MXene intercalated with MWCNTs is used as the signal recognition end. The large specific surface area creates a good platform for the adsorption of the cationic dye MB, thereby serving as the third-level signal amplification. The detection range of the designed electrochemical biosensor is 1.0~1.0×10 6 pM, and the detection limit was 50.3fM.
[0007] In order to achieve these objectives and other advantages of the present invention, a probe for detecting HBV-DNA is provided, which is a padlock probe. The padlock probe includes an RCA circular template region and an HBV-DNA recognition region. The nucleotide sequence of the padlock probe is shown in SEQ ID NO:1, and the nucleotide sequence of HBV-DNA is shown in SEQ ID NO:2.
[0008] The method for preparing a working electrode for detecting HBV-DNA using a probe comprises the following steps:
[0009] The padlock probe DNA was incubated with HBV-DNA; then exonuclease III was added for incubation, followed by heat inactivation; PolyT-primer and Escherichia coli DNA ligase were added, mixed, incubated, and heat inactivated; then dNTPs and phi29 DNA polymerase without dATP were added, incubated, and heat inactivated; after the incubated sample solution was cooled, it was incubated with MB@ZIF-90, and then the supernatant was collected by centrifugation and transferred to the functionalized electrode modified with MX / MWCNTs, incubated, and then the MB not adsorbed on the electrode was washed off to obtain a working electrode.
[0010] Application of the prepared working electrode in detecting HBV-DNA.
[0011] The three-electrode system for detecting HBV-DNA includes a working electrode, a counter electrode and a reference electrode. The working electrode is the working electrode prepared as described above, the counter electrode is a platinum wire electrode, and the reference electrode is Ag / AgCl.
[0012] The method for detecting HBV-DNA using a probe comprises the following steps:
[0013] Step 1: Incubate the padlock probe DNA with different concentrations of HBV-DNA respectively; then add exonuclease III for incubation, and then heat inactivate; then add PolyT-primer and Escherichia coli DNA ligase, mix, incubate, and then heat inactivate; then add dNTP and phi29 DNA polymerase without dATP, incubate, and then heat inactivate; after the incubation sample solution is cooled, incubate with MB@ZIF-90, then collect the supernatant by centrifugation, and transfer the supernatant to the functionalized electrode modified with MX / MWCNTs, incubate, then rinse off the MB not adsorbed on the electrode, and test it as a working electrode in a three-electrode system;
[0014] Step 2: Electrochemical measurement was performed using a three-electrode system to obtain the DPV signal response curve of the byproduct sample solution after the RCA reaction activated by HBV-DNA with different concentrations and the supernatant released by the reaction of MB@ZIF-90 on the working electrode, and the current peak of the DPV signal response curve was linearly fitted to obtain the linear correlation between the DPV peak current signal and the logarithmic value of the HBV-DNA concentration. The regression equation was ΔI = 0.769 + 2.821lgC HBV-DNA , the correlation coefficient is 0.998;
[0015] Step 3: Obtain a working electrode formed by HBV-DNA of unknown concentration according to the method in step 1, and then use a three-electrode system to perform electrochemical measurement to obtain the DPV peak current signal, and substitute it into the regression equation to obtain the logarithm of the HBV-DNA concentration, and then calculate the HBV-DNA concentration.
[0016] Preferably, in the method for detecting HBV-DNA, the preparation method of MB@ZIF-90 comprises the following steps:
[0017] 43.9 mg of zinc acetate and 13 mg of MB were mixed in 4 mL of N,N-dimethylformamide and stirred at room temperature for 10 min. Then, 6 mL of DMF containing 38 mg of 2-methylimidazole aldehyde was added. The mixture was kept at room temperature for 30 min and centrifuged at 10,000 rpm for 15 min. The precipitate was repeatedly washed with methanol until the supernatant was colorless and then washed three times with ultrapure water to obtain / MB@ZIF-90.
[0018] Preferably, in the method for detecting HBV-DNA, the method for preparing the functionalized electrode modified with MX / MWCNTs comprises the following steps:
[0019] Step 1), adding the MWCNTs dispersion dropwise into the MXene dispersion, oscillating and mixing continuously, then adding 24% by volume of anhydrous ethanol and 5% by volume of Nafion and oscillating and mixing to obtain a 2-7 mg / mL MX / MWCNTs dispersion; wherein the MXene content is 0.1-3.5 mg / mL, and the MWCNTs content is 0.1-3.5 mg / mL;
[0020] Step 2), drop the MX / MWCNTs dispersion on the glassy carbon electrode and dry it to obtain a functionalized electrode modified with MX / MWCNTs.
[0021] Preferably, in the method for detecting HBV-DNA, the method for preparing MXene comprises the following steps:
[0022] 1 g Ti3AlC2 powder was slowly added to a mixed acid of 1.6 g LiF and 20 mL 9 M HCl, and the mixture was reacted in a water bath at 40 ° C for 48 h. The precipitate after the reaction was washed three times by centrifugation with 2 M HCl as a detergent to remove LiF in the precipitate. The precipitate was then washed with ultrapure water until the upper centrifugal liquid turned black and the lower precipitate became viscous and swollen. The centrifugal liquid was no longer replaced, and the centrifugation cycle was shaken and centrifuged three times again. The obtained black suspension was ultrasonically treated at 16 ° C for 2 h under N2 protection, and then the unetched precipitate was separated by centrifugation. The upper black liquid was Ti3C2T x MXene.
[0023] Preferably, in the method for detecting HBV-DNA, in the step 1, exonuclease III is added and incubated at 37°C for 45 minutes; PolyT-primer and Escherichia coli DNA ligase are added, mixed, and incubated at 16°C for 45 minutes; dNTPs without dATP and phi29 DNA polymerase are added, and incubated at 30°C for 2 hours; 1 mg / mL MB@ZIF-90 is incubated at below 25°C for 5 minutes; the supernatant is transferred to the functionalized electrode modified with MX / MWCNTs and incubated at 45°C for 40 minutes;
[0024] In the step 1), a 4 mg / mL MX / MWCNTs dispersion is obtained, wherein the MXene content is 2.7 mg / mL and the MWCNTs content is 1.3 mg / mL.
[0025] Application of probes in detecting HBV-DNA.
[0026] The present invention has at least the following beneficial effects:
[0027] The specially designed high-specificity padlock assists the HBV-DNA recognition and signal amplification module of RCA, and MB@ZIF-90 is used to amplify the signal again, and the MX / MWCNTs composite material is used to absorb the cationic dye MB, so that the composite material is used as an electrochemical sensor. In order to combine RCA with the MB@ZIF-90 composite material for signal amplification and avoid the interference of dATP, the circular DNA template used in the present invention is designed as a T-deficient template, and RCA is designed to work without adding dATP and ATP.
[0028] The present invention provides a padlock probe DNA with a special structure that can reduce false positive signals. When HBV-DNA is not detected, it can inhibit the activation of the rolling circle amplification program. After the rolling circle amplification program is activated, it can trigger the disintegration of the zeolite imidazole acid framework structure wrapped with the cationic dye methylene blue. The MX / MWNCNTs composite material is used as a signal detection end, and the adsorption of methylene blue is increased by the dye adsorption principle, which greatly amplifies the electrochemical detection signal. The detection range of the designed electrochemical biosensor is 1.0-1.0×106pM, and the detection limit is 0.503pM. This strategy also has good specificity and recovery rate in actual serum samples.
[0029] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of label-free electrochemical detection of HBV;
[0031] Figure 2 (a) SEM image of MAX phase; Figure 2 (b) SEM image of the cross section of the MXene film; Figure 2 (c) EDS image of O element on the MXene surface; Figure 2 (d) SEM image of GCE / MXene; Figure 2 (e) SEM image of GCE / MWCNTs; Figure 2 (f) SEM image of GCE / MX / MWCNTs;
[0032] Figure 3 (a) XRD patterns of MAX phase and MXene (the inset is a digital photo of the Tyndall effect of low-concentration MXene colloid); Figure 3 (b) Full XPS scan spectra of MXene, MX / MWCNTs, and MX / MWCNTs+MB;
[0033] Figure 4(a) GCE / MXene and GCE / MX / MWCNTs in 5 mM [Fe(CN)6] 3- / 4- CV curves in solution (containing 0.1 M KCl); Figure 4 (b) Bare GCE, GCE / MXene, GCE / MWCNTs and GCE / MX / MWCNTs in 5 mM Ru(NH3)6] 3+ CV curves in solution (containing 0.1 M KCl); Figure 4 (c) Bare GCE, GCE / MXene, GCE / MWCNTs and GCE / MX / MWCNTs in 5 mM Ru(NH3)6] 3+ EIS curve in a solution containing 0.1 M KCl; wherein the open circuit voltage is 0.23 V, the excitation amplitude is 5 mV, and the frequency range is 0.1 to 10 kHz;
[0034] Figure 5 (a), 5(b) and 5(c) are the results of Bare GCE, MXene and MX / MWCNTs in 5 mM Ru(NH3)6] 3+ CV curves at different scan rates in solution (containing 0.1 M KCl); Figure 5 (d) Linear relationship between the square root value of different scan rates and the anodic oxidation current of Bare GCE, GCE / MXene and GCE / MX / MWCNTs;
[0035] Figure 6 (a) Zeta potential diagram of MXene, MWCNTs, MX / MWCNTs and MX / MWCNTs+MB measured in 10 mM Tris-HCl (containing 1 mM NaCl) at pH ≈ 8; 6(b) and 6(c) are the optimization of the mass ratio of MXene and MWCNTs in 4 mg / mL MX / MWCNTs and the optimization of the concentration of MX / MWCNTs on the glassy carbon electrode, respectively;
[0036] Figure 7 (a) is the SEM image of MB@ZIF-90; 7(b) is the SEM image of MB@ZIF-90+TSPP, and the inset is the enlarged image of the red circle; 7(c) is the UV-visible spectra of MB, MB@ZIF-90+TSPP, MB@ZIF-90 and ZIF-90;
[0037] Figure 8 (a) is the effect of temperature on MB@ZIF-90; 8(b) is the concentration optimization diagram of MB@ZIF-90; 8(c) is the effect of pH on MB@ZIF-90; 8(d) is the storage stability diagram of MB@ZIF-90;
[0038] Fig. 9 (a) is a schematic diagram of the effect of exonuclease III; 9(b) is a UV-vis verification diagram of the exonuclease III cleavage effect; 9(c) is an electrochemical RCA amplification verification diagram;
[0039] Fig.10 (a) is a comparison of DPV signals obtained by GCE / MX / MWCNTs after the centrifugation of the upper liquid after the reaction of TSPP and HBV-activated RCA byproducts with MB@ZIF-90; (b) is an optimized UV-visible spectrum of the reaction time of MB@ZIF-90 with 100nM HBV-activated RCA byproducts; (c) is an optimized adsorption time of GCE / MX / MWCNTs on the upper liquid after the reaction of 100nM HBV-activated RCA byproducts with MB@ZIF-90;
[0040] Fig.11 (a) is the reaction time optimization diagram of nuclease III; 11(b) is the reaction time optimization diagram of E. coli DNA ligase; 11(c) is the reaction time optimization diagram of phi29 DNA polymerase; 11(d) is the dNTP (excluding dATP) concentration optimization diagram;
[0041] Fig.12 (a) Add different concentrations (1~5×10 6 pM) of HBV-DNA; 12(b) is the relationship between DPV peak current and HBV DNA concentration, where the inset is the relationship between DPV peak current and HBV DNA concentration (1-10 6 12(c) is the selective DPV response curve of HBV-DNA detection; 12(d) is the response signal change diagram corresponding to the parallel experiment of 10 different electrodes detecting 100nM HBV-DNA. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0043] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0044] 1 Introduction
[0045] MXene is a new type of two-dimensional nanomaterial that has emerged in recent years. The most representative and widely studied one in the MXene family is Ti3C2T x, where T x represents the surface groups, including -OH, =O and -F. MXene is widely used in supercapacitors, electrocatalysis, electrochemical sensors and other fields due to its excellent conductivity, hydrophilicity, high specific surface area and large double-layer capacitance. At the same time, MXene has shown broad application prospects in the field of electrochemical biosensors. At present, in the field of electrochemical biosensors, the most commonly used strategy is to use the conductivity and large specific surface area of MXene to modify capture probes and signal probes labeled with substances that can generate electrochemical signals on its surface. However, this strategy has an unavoidable defect, which is the direct modification of the capture probe on the surface, which will take a considerable amount of time to fix. At the same time, to fix the capture probe on the MXene surface, it is necessary to perform special treatment on the MXene surface in advance, such as modifying metal nanoparticles or constructing other surface active groups, which not only further increases the difficulty of material preparation, but also increases the time cost. So far, no work has been found to directly use unmodified MXene as a signal receiving end. In the field of wastewater treatment, because the MXene surface is negatively charged, it is used as an effective adsorbent for cationic dyes and metal cation pollutants. In the field of electrochemical sensors, the cationic dye methylene blue (MB) is a commonly used electrochemical signal substance, so we were inspired to use the property of MXene adsorbing MB to obtain electrochemical detection signals. However, when MXene is dry, it is limited by the interlayer self-stacking effect of MXene, which greatly weakens the specific surface area of MXene.
[0046] Rolling circle amplification (RCA) is a very promising isothermal amplification technology with the advantages of high efficiency of isothermal amplification, convenient editing, and flexible signal output. In nucleic acid detection, the specific recognition regions at both ends of the padlock probe are usually used to identify the nucleic acid to be tested, which is then connected into a circular template, and then the signal is amplified and output through RCA. It is often used in the molecular diagnosis of various diseases. However, this recognition method has some defects. For example, the nucleic acid to be tested only relies on base complementary pairing and ligase to form a circle to ensure specificity during the recognition process, which cannot distinguish false positives caused by base mismatches.
[0047] In order to solve the above problems, we designed a special padlock probe DNA as the recognition probe of HBV-DNA. The remaining base sequence after treatment with nuclease III was used as an RCA template for amplification to release the amplification product pyrophosphate (PPi), forming a signal amplification effect. The zeolite imidazole framework structure (MB@ZIF-90) encapsulated with methylene blue (MB) plays the role of detecting the RCA amplification byproduct PPi, releasing a large amount of MB as a second amplification of the signal. The electrode modified with the MX / MWCNTs composite material composed of MXene intercalated with MWCNTs is used as the signal recognition end. The large specific surface area creates a good platform for the adsorption of the cationic dye MB, which serves as the third-level signal amplification. The detection range of the designed electrochemical biosensor is 1.0~1.0×10 6 pM, and the detection limit was 50.3fM.
[0048] 2 Experimental part
[0049] 2.1 Reagents and Materials
[0050] Methylene blue (MB, ≥70.0%), 2-imidazole carboxaldehyde (2-ICA, ≥98.0%), and sodium pyrophosphate (TSPP, ≥99.0%) were purchased from Aladdin Reagent Co., Ltd. (Shanghai, China). Zinc acetate dihydrate (Zn(CH3COO)2·2H2O, ≥99.9%), Ti3AlC2 (MAX, ≥98.0%, 200 mesh), and N,N-dimethylformamide (DMF, ≥99.5%) were purchased from MacLean Biochemical Technology Co., Ltd. (Shanghai, China). Multi-walled carbon nanotubes (tube diameter: 10-20 nm, tube length 10-20 μm) were provided by Shanghai Maoguo Nanotechnology Co., Ltd. Exonuclease III (EXO III), Escherichia coli DNA ligase (E. coli DNA ligase), and phi29 DNA polymerase were ordered from New England Biolabs (Shanghai, China). All DNA probes, dATP, dCTP, dGTP, and dTTP were from Shanghai Shenggong Biotechnology Co., Ltd.
[0051] Preparation of 2.2MB@ZIF-90
[0052] First, 43.9 mg zinc acetate and 13 mg MB were mixed in 4 mL N,N-dimethylformamide (DMF) and stirred at room temperature for 10 min. Then, 6 mL DMF containing 38 mg 2-methylimidazole aldehyde (2-ICA) was added to the above solution. The mixture was placed at room temperature for 30 min and centrifuged at 10,000 rpm for 15 min. The precipitate was repeatedly washed with methanol until the supernatant was colorless, and then washed with ultrapure water 3 times. The obtained MB@ZIF-90 probe material was dispersed in ultrapure water and stored at 4°C.
[0053] 2.3Ti3C2T x Preparation of MXene
[0054] Ti3C2T was obtained by etching the Al metal of Ti3AlC2 MAX phase through the mildly enhanced delamination (MILD) method. x MXene. 1g Ti3AlC2 powder was slowly added to a mixed acid of 1.6g LiF and 20mL 9M HCl, and reacted in a water bath at 40°C for 48h. The precipitate after the reaction was washed 3 times by centrifugation (5min per cycle at 3500rpm) with 2M HCl as a detergent to remove LiF from the precipitate, and then the precipitate was washed cyclically with ultrapure water until the upper centrifuge liquid turned black and the lower precipitate became viscous and swollen. The centrifuge liquid was no longer replaced, and the centrifuge was shaken and centrifuged again for three cycles. The resulting black suspension was ultrasonically treated at a constant temperature of 16°C for 2h under N2 protection, and then the unetched precipitate was separated by centrifugation (centrifugation at 5000rpm for 30min). The upper black liquid obtained is a single few-layer Ti3C2T x MXene. Separate the upper black liquid and freeze-dry it for later use.
[0055] Preparation of 2.4MX / MWCNTs electrodes
[0056] The MWCNTs dispersion was added dropwise to the MXene dispersion, and the mixture was continuously shaken and mixed. Then, 24% anhydrous ethanol and 5% Nafion were added and shaken to obtain a 4 mg / mL MX / MWCNTs dispersion, in which the MXene content was 2.7 mg / mL (final concentration) and the MWCNTs content was 1.3 mg / mL (final concentration). The anhydrous ethanol content was 240 μL, and the 5% Nafion content was 30 μL.
[0057] Take 5 μL of MX / MWCNTs dispersion and drop it on the glassy carbon electrode with a cell diameter of 3 mm, and dry it at 45°C for 30 min.
[0058] 2.5 Detection of HBV DNA
[0059] The DNA sequences used in this application are shown in Table 1.
[0060] The probe for detecting HBV-DNA is a padlock probe, which includes an RCA circular template region and an HBV-DNA recognition region. The nucleotide sequence of the padlock probe is shown in SEQ ID NO:1, and the nucleotide sequence of the hepatitis B virus is shown in SEQ ID NO:2.
[0061] The HBV-DNA recognition region is the HBV-DNA complementary base sequence.
[0062] The method for detecting HBV-DNA comprises the following steps:
[0063] 5μL of 3μM padlock probe DNA was incubated with 5μL of different concentrations of HBV-DNA at 37℃ for 20min; then 10U of exonuclease III was added, incubated at 37℃ for 45min, and heat-inactivated at 70℃ for 20min. After the recognition of the target DNA to be detected, the target DNA recognition region was degraded to expose the loop connection site. 5μL of 6μM PolyT-primer (T-rich primer) and 4U Escherichia coli DNA ligase were added to the above solution and mixed. Incubated at 16℃ for 45min, and then heated at 65℃ for 10min for heat inactivation. The padlock probe DNA without the target DNA recognition region formed a circular template to activate RCA. Then, 5 μL of 9 mM (9 mM is the concentration added before the reaction, which will be diluted in the actual reaction system, and the actual reaction concentration after addition is 1 mM) dNTP (composed of dTTP, dCTP, dGTP) and 10 U of phi29 DNA polymerase were added to the above solution, incubated at 30 ° C for 2 hours, and then heated at 65 ° C for 10 minutes for thermal inactivation. Subsequently, the incubated sample solution was cooled to room temperature and incubated with 1 mg / mL MB@ZIF-90 for 5 minutes. Finally, the supernatant of the above mixed solution was collected by centrifugation at 13000 rpm for 5 minutes, and 10 μL of the supernatant was transferred to the functionalized electrode modified with MX / MWCNTs, incubated at 45 ° C for 40 minutes, and then the MB not adsorbed on the electrode was washed off and tested as a working electrode in the three-electrode system.
[0064] Electrochemical measurements were performed using a three-electrode system (the three-electrode system consisted of a platinum wire electrode, an Ag / AgCl electrode, and a functionalized electrode modified with MX / MWCNTs as a working electrode) on a CHI-760E electrochemical workstation to obtain the DPV signal response curves of the byproduct sample solution after the RCA reaction activated by HBV-DNA at different concentrations and the supernatant released by the reaction of the MB@ZIF-90 composite material on the working electrode. The current peak of the DPV signal response curve was linearly fitted to obtain the linear correlation between the DPV peak current signal and the logarithmic value of the HBV-DNA concentration. The regression equation was ΔI = 0.769 + 2.821lgC HBV-DNA (pM), correlation coefficient (R 2 ) is 0.998; the detection limit calculation formula is LOD=3σ / S=0.503pM, where σ is the current value obtained from 11 blank experiments, and S is the slope of the linear regression equation.
[0065] According to the above method, in actual use, HBV-DNA of unknown concentration can be detected to obtain the DPV peak current signal, which is then brought into the regression equation to obtain the logarithmic value of the HBV-DNA concentration, and then the HBV-DNA concentration can be calculated.
[0066] Table 1 shows the DNA sequences used in the RCA module
[0067]
[0068] 2.6 Human serum sample processing
[0069] The collected fresh plasma was centrifuged at 10000rpm for 8min to remove components such as red blood cells and platelets, and the upper layer sample was extracted. In order to precipitate large proteins in the serum, serum: perchloric acid was mixed at 1:15 (V / V), stirred at room temperature for 5min, and then the mixed sample was centrifuged at 10000rpm for 10min, and the supernatant was collected to obtain human serum samples, which were stored at 4°C for testing. Before testing, the human serum samples were diluted 50 times with Tris-HCl buffered saline (0.1M, pH 7.4) before use.
[0070] 2.7 Equipment
[0071] The morphology of the material was characterized by using a Gemini300 thermal field emission scanning electron microscope. The X-ray diffraction (XRD) spectrum of the material was obtained using a D8ADVANCE X-ray diffractometer from Bruker, Germany. The X-ray photoelectron spectroscopy (XPS) of the material was analyzed using the Thermo escalab250Xi from the United States. The ultraviolet-visible spectrophotometer used was a Shanghai Yuanxi Instrument X-8S to record the experimental data. All electrochemical tests were conducted using Shanghai Chenhua CHI 760E.
[0072] 3 Results and discussion
[0073] 3.1 Principle of electrochemical method
[0074] like Figure 1The figure shows the principle diagram of label-free electrochemical detection of HBV. There is a target DNA recognition region (the dark red fragment region in the figure) at the 3' end of the padlock probe DNA. When it recognizes the target DNA (HBV), the recognition region is degraded from the 3' end of the padlock probe DNA under the action of exonuclease III to release the target DNA (because the 3' end of the target DNA has a 4-base overhang, it avoids degradation by exonuclease III), allowing the target DNA to enter the next recognition cycle; at the same time, the 3' end of the remaining padlock probe DNA base sequence (called circular template DNA) after degradation exposes the recognition region of PolyT-primer (the orange-yellow fragment region in the figure) and the connection site of Escherichia coli DNA ligase. Under the action of the two, the two ends of the circular template DNA are connected into a ring; then phi29 DNA polymerase uses the circular template DNA as a template to perform rolling circle amplification along the 3'→5' of PolyT-primer. In order to avoid the interference of dATP, the circular template DNA region used in this application is designed as a T-deficient template, and RCA is designed to work without adding dATP. All enzymes can work without using ATP. During the rolling circle amplification process, a large amount of byproduct PPi is generated. 2+ The coordination is stronger than that of imidazole-2-carboxaldehyde (2-ICA) and Zn 2+ Due to the coordination of PPi, 2-ICA in MB@ZIF-90 is well replaced. Therefore, the amplification of RCA can promote the decomposition of MB@ZIF-90 and lead to the release of MB. The composite material composed of MXene and multi-walled carbon nanotubes (MWCNTs) is the power source for the selective adsorption of cationic dye MB because of its negative charge. Its large specific surface area increases the adsorption amount of cationic dye MB. After the cationic dye MB is adsorbed by MX / MWCNTs, an electrochemical signal is generated, thereby achieving the purpose of label-free electrochemical detection. This method is simple to operate, fast to detect and highly sensitive.
[0075] 3.2 Characterization and application optimization of MX / MWCNTs composites
[0076] In order to observe the surface morphology of MX / MWCNTs, SEM characterization of MAX phase, MXene, MWCNTs, and MX / MWCNTs was performed. Figure 2 (a) shows the unetched Ti3AlC2 MAX phase, where the layered bulk structure can be clearly seen. Figure 2 (b) The product Ti3C2T after MILD etching of the Al layer of the MAX phase x The electron microscope image of the cross section of the film after vacuum filtration and drying shows that it has a clear flaky nanostructure, which indicates that the preparation of MXene is successful. Figure 2(c) is the EDS image of the O element on the MXene surface, reflecting that the surface of the MXene nanosheet is rich in O elements, which is due to the surface oxygen-containing terminal groups brought about by MILD etching. Figure 2 (d) It can be seen that when MXene is deposited on the electrode, the MXene nanosheets are stacked and the gaps between the layers are almost invisible, which seriously weakens the specific surface area of MXene. Figure 2 This is clearly visible in (e). Figure 2 (f) The structure of MX / MWCNTs is clearly shown. MXene nanosheets and MWCNTs are cross-stacked with each other, which makes MX / MWCNTs have a porous structure and improves the stacking problem of MXene nanosheets.
[0077] In order to verify the preparation effect of MXene, XRD characterization of MAX phase and MXene was carried out in the scanning range of 5° to 70°, such as Figure 3 (a) shown. Figure 3 In (a), the comparison of the diffraction peaks of the MAX phase and MXene shows that after etching, the characteristic (104) crystal plane diffraction peak of "Al" at 2θ = 38.75° in the MAX phase and the crystal plane diffraction peaks nearby disappear, which means that "Al" is etched away and the crystal framework of the MAX phase disappears. In addition, the (002) crystal plane diffraction peak shifts significantly from 9.54° to a low angle of 7.04°, indicating an increase in the lattice constant (c-LC), which means an increase in the interplanar spacing; the peak shape changes from high and sharp to short and wide, which indicates a decrease in crystal size, combined with Figure 2 (b) SEM images of the morphology and Figure 3 (a) is a digital photo illustration of the Tyndall effect, which together demonstrates the formation of a new layered structure, representing the successful preparation of MXene. Figure 3In the full XPS spectrum shown in (b), we can observe several significant changes. First, the C1s peak of the MX / MWCNTs composite material is significantly enhanced compared with MXene. This change is attributed to the successful insertion of multi-walled carbon nanotubes (MWCNTs) into the MXene interlayer, which significantly increases the overall content of C in the composite material. A new N1s peak appears at about 399 eV, and the intensity of the C1s peak is more significantly improved, while the peak intensity of other elements shows a significant downward trend. This change is directly related to the chemical composition of the MB molecule and its interaction with MX / MWCNTs. Specifically, MB molecules are rich in C and N elements. When they are effectively adsorbed by MX / MWCNTs, not only does it lead to a further increase in the content of C elements in the composite material, which is manifested as a significant enhancement of the C1s peak in the XPS spectrum; moreover, as the MB molecule layer gradually accumulates and covers the surface of MX / MWCNTs, they effectively shield the original signals of other elements on the surface of the composite material, thereby causing the peak intensity of these elements to be correspondingly weakened in the XPS spectrum. This finding strongly confirms the efficient adsorption of MB molecules on the surface of MX / MWCNTs.
[0078] The electrochemical behavior of MX / MWCNTs was analyzed using cyclic voltammetry (CV). Figure 4 As shown in (a), due to the redox probe [Fe(CN)6] 3- / 4- In the range of -0.2 to 0.6 V of the peak potential, two-dimensional MXene is inevitably irreversibly oxidized at an anode potential above 0.2 V. After the first cycle, the electrochemical oxidation current density becomes unstable and decreases successively. To solve this problem, Ru(NH3)6 is used. 3+ As a redox probe, it can be oxidized and reduced in a lower potential window. Figure 4 As shown in (b), GCE, GCE / MXene, GCE / MWCNTs and GCE / MX / MWCNTs all present a pair of clear redox peaks, indicating that Ru(NH3)6 3+ The probe has reversible electrochemical behavior on the surface of the material. Thanks to the good metallic conductivity of MXene, at the same scan rate, the oxidation peak current density of GCE / MXene, GCE / MWCNTs and GCE / MX / MWCNTs is 5.37 times, 2.30 times and 3.67 times higher than that of the bare glassy carbon electrode, respectively. The peak current density of GCE / MWCNTs is lower than that of GCE / MXene because GCE / MWCNTs has poor hydrophilicity. In the experiment, it was observed that a thin air layer was formed between the electrode interface and the liquid surface, which hindered the Ru(NH3)6] 3+The probe transfers electrons on the surface of the material, and the excellent hydrophilicity of MXene can make up for the non-hydrophilicity of MWCNTs. The peak current density of GCE / MX / MWCNTs is lower than that of GCE / MXene. This is because MWCNTs and MXene sheets are not connected by covalent bonds, but self-assembled by electrostatic adsorption, which means that Ru(NH3)6] 3+ When the probe transfers electrons on the surface of a material, it encounters resistance between different phases. Figure 4 (c) The EIS curves show that the absence of semicircles in the high-frequency region for GCE / MXene, GCE / MWCNTs and GCE / MX / MWCNTs means that there is rapid electron transfer at the interface between GCE and the material and the interface between the material and the electrolyte. From the low- and high-frequency regions, it is observed that the capacitance curve of GCE / MXene is more vertical than that of GCE / MX / MWCNTs, which further explains that the CV redox peak current of GCE / MXene is higher than that of GCE / MX / MWCNTs, because the CV redox peak current of GCE / MXene also has the contribution of capacitance current.
[0079] Figure 5 (ad) shows the results of the study of the electrochemical kinetics of three differently modified electrodes at a scan rate of 10 to 100 mV / s using CV. According to the Randles-Sevcik formula:
[0080] i p =2.69×10 5 n 3 / 2 AD0 1 / 2 v 1 / 2 C (3)
[0081] where i p is the peak current, n is the number of electrons involved in the redox reaction, and A is the electrochemical surface area in cm 2 , D0 is the diffusion coefficient of the redox probe, in cm 2 / s, v is the scanning rate in v / s, and C is the concentration of the redox probe in mol / cm 3 Ru(NH3)6] 3+ The diffusion coefficient in the MXenes system is D0 = 5.5 × 10 -5 cm 2 / s.
[0082] like Figure 5 As shown in (d), the anodic oxidation current of the three electrodes increases linearly with the square root of the scan rate, indicating that Ru(NH3)6] 3+The electrochemical reaction of the redox probe on the three electrodes is a diffusion-controlled process. According to the linear equation fitted by the square root of the anodic oxidation current and the scan rate of the three electrodes, the electrochemically active surface area of the glassy carbon bare electrode was obtained to be 0.099 cm 2 The electrochemically active surface area of the MXene-modified glassy carbon electrode is 0.228 cm 2 The electrochemically active surface area of the MX / MWCNTs modified glassy carbon electrode is 0.251 cm 2 It can be seen that the electrochemical active surface of the MX / MWCNTs modified glassy carbon electrode is greatly increased, which provides a good platform for the adsorption of MB.
[0083] In order to explore the surface charge changes before and after MX / MWCNTs adsorption, the Zeta potential of MXene, MWCNTs, MX / MWCNTs and MX / MWCNTs+MB was characterized. 1mM NaCl was added as a supporting electrolyte in 10mM Tris-HCl at pH ≈ 8, which was used as the solvent for the Zeta potential test to simulate the ionic environment in the actual test. Figure 6 As shown in (a), the addition of MWCNTs reduces the Zeta potential of MX / MWCNTs compared to MXene, but does not affect its negatively charged characteristics. After MX / MWCNTs adsorb MB, the Zeta potential decreases sharply. This is because the cationic dye and MX / MWCNTs undergo electrostatic adsorption, which causes the Zeta potential to decrease sharply. This shows that MX / MWCNTs have extremely strong cationic selectivity.
[0084] In order to simulate the pyrophosphate ions (PPi) produced during the RCA reaction, we used sodium pyrophosphate (TSPP) as a substitute to react with MB@ZIF-90, and optimized the mass ratio of MXene and MWCNTs in MX / MWCNTs, the concentration of MX / MWCNTs deposited on the electrode, and other conditions, so that the detection system can achieve the best detection state after coordination. Figure 6 As shown in (b), as the mass proportion of MWCNTs in MX / MWCNTs gradually increases, the DPV signal intensity first increases, and then decreases after the MXene:MWCNT mass ratio reaches 1:2. This is because the appropriate addition of MWCNTs can increase the specific surface area of MXene, but when MWCNTs occupy an absolute dominant proportion, the hydrophobicity of MX / MWCNTs on the electrode increases, resulting in increased steric hindrance for the adsorption of MB. Figure 6 As shown in (c), the optimal concentration of MX / MWCNTs dispersion is 4 mg / mL. As the concentration increases, the thickness of MX / MWCNTs deposited on the electrode surface becomes thicker, which makes it easier to fall off, so the DPV signal decreases.
[0085] 3.3 Characterization and application optimization of MB@ZIF-90
[0086] The granular morphology of MB@ZIF-90 is Figure 7 (a) shows that the preparation of MB@ZIF-90 was successful. After adding TSPP and reacting for 2 minutes, the structure of MB@ZIF-90 appeared. Figure 7 (b) The red circle part shows cracking phenomenon, and the number of MB@ZIF-90 particles with cracking increases. This is because the PPi in the TSPP solution destroys the coordination structure between 2-ICA and Zn2+.
[0087] In order to verify whether MB@ZIF-90 has successfully encapsulated methylene blue (MB) and has the ability to respond to the target detection object, we performed ultraviolet visible spectroscopy (UV-vis) characterization. Figure 7 As shown in (c), compared with pure ZIF-90, both MB@ZIF-90 and MB@ZIF-90+TSPP showed the characteristic absorption peak of MB at 664nm, and MB@ZIF-90+TSPP showed an enhanced characteristic absorption peak of MB. This result strongly proves the successful preparation of MB@ZIF-90 and the effective encapsulation of MB by ZIF-90.
[0088] The UV-vis technique was used to measure the MB signal in the MB@ZIF-90 dispersion under different conditions, such as Figure 8 In order to explore the optimal reaction temperature of MB@ZIF-90, the relationship between the disintegration of MB@ZIF-90 structure and temperature was investigated, as shown in Figure 8 As shown in (a), MB@ZIF-90 basically does not disintegrate below 25°C. As the temperature rises, more and more MB@ZIF-90 particles are decomposed, and MB is released in large quantities, resulting in an enhancement of the UV-vis signal. Until 65°C, the MB decomposition structure is destroyed by the temperature and the signal decreases. Figure 8 As shown in (b), the optimal concentration of MB@ZIF-90 participating in the reaction was explored. It can be seen that at 1 mg / mL, the signal of MB released by MB@ZIF-90 is the strongest. It is worth noting that at high concentrations, MB@ZIF-90 will aggregate and precipitate in the solution, and the released MB is adsorbed by the porous structure in the MB@ZIF-90 aggregates, resulting in a decrease in MB in the solution, which leads to a decrease in MB signal. Figure 8(c) The pH stability of MB@ZIF-90 was investigated. When the pH was ≈ 5 to 9, the structure of MB@ZIF-90 was relatively stable. Too high or too low pH would lead to leakage of MB. At 4°C, MB@ZIF-90 dispersion would spontaneously leak MB. This was due to the osmotic pressure between the preservation solution and the high concentration of MB inside MB@ZIF-90. Figure 8 As shown in (d), MB in the solution gradually reached equilibrium after 10 days and remained unchanged until the 35th day.
[0089] In summary, in order to minimize the signal leakage of MB@ZIF-90 caused by osmotic pressure, MB@ZIF-90 is required to be used on the tenth day after synthesis, with the use temperature controlled at 25°C and the use concentration at 1 mg / mL. Considering the subsequent RCA enzyme activity conditions, the use pH is controlled at around 8.
[0090] 3.4 Validation of rolling circle amplification reaction
[0091] Recognition of HBV-DNA sequences is crucial during the RCA process. Fig. 9 (a). Fig. 9 (b) shows the sample solution in which 100 nM HBV was incubated with 3 μM padlock DNA and then 10 U exonuclease III was added and incubated for 1 hour under UV A. 260nm Absorbance comparison. Since the strong absorption of ultraviolet light by the conjugated double bond structure of the base is suppressed by the stacking effect of the double-stranded base (low color effect), Fig. 9 In (b), the absorption peak of sample 1 (without exonuclease III) is lower than that of sample 2 (with exonuclease III). Since the double-stranded structure of HBV-DNA / padlocked DNA is digested by exonuclease III, releasing single strands and dNTPs, the ultraviolet absorption shows a high color effect, so it can be judged that the double-stranded structure of HBV-DNA / padlocked DNA is successfully formed and the exonuclease III works smoothly. Fig. 9 As shown in (c), RCA cannot be activated in the absence of exonuclease III, Escherichia coli DNA ligase and HBV-DNA. Only when HBV-DNA is present can RCA be activated. After RCA is activated, a large amount of PPi is released, which causes the MB@ZIF-90 structure to disintegrate and release a large amount of electrochemical signal substance MB, resulting in an enhancement of the DPV peak current signal, which is in line with our design expectations.
[0092] 3.5 Optimization of detection system
[0093] In order to verify whether the PPi released by the RCA process also has a destructive effect on MB@ZIF-90, RCA was activated with 100 nM HBV and reacted with MB@ZIF-90. The DPV response comparison curve of the centrifuged upper liquid after GCE / MX / MWCNTs adsorbed 10 mM TSPP and 100 nM HBV and reacted with MB@ZIF-90 is shown in Figure 2. Fig.10 As shown in (a). The DPV response signal of 100nM HBV is higher than that of 10mMTSPP, which may be because in RCA, the required enzyme needs to react in a buffer containing glycerol, and the final detection product adsorbed by the GCE / MX / MWCNTs electrode contains glycerol, which enables the MWCNTs in the MX / MWCNTs to fully contact the solution and increase the adsorption of MB. Fig.10 As shown in (b), MB@ZIF-90 can react completely in 5 min, which greatly shortens the detection time. Fig.10 (c) shows the optimization of the adsorption time of GCE / MX / MWCNTs on the centrifuged upper liquid after the reaction of 100 nM HBV-activated RCA byproduct PPi with MB@ZIF-90. It can be seen that after 40 minutes of adsorption, the adsorption amount of MB by GCE / MX / MWCNTs gradually reached saturation, and the optimal time for GCE / MX / MWCNTs to MB was 40 minutes.
[0094] In order to achieve the best detection effect of the detection system, the reaction time of exonuclease III, the reaction time of E. coli DNA ligase, the reaction time of phi29 DNA polymerase and the concentration of dNTP (excluding dATP) during the RCA process were optimized. Fig.11 (ad) It can be seen that the optimal reaction time of nuclease III is 45 min, the optimal reaction time of Escherichia coli DNA ligase is 60 min, the optimal reaction time of phi29 DNA polymerase is 120 min, and the optimal reaction concentration of dNTP (excluding dATP) is 1 mM.
[0095] 3.6 Linearity, selectivity and stability of the detection system
[0096] Under the optimal reaction conditions of the detection system, different concentrations of HBV-DNA were detected. 6 The DPV signal response of the supernatant released by the reaction of pM concentration of HBV-DNA with MB@ZIF-90 composite material on the MX / MWCNTs modified electrode is shown in Figure 2. Fig.12 As shown in (a), Fig.12 (b) Fig.12 (a) is the linear fitting diagram of the peak current of the DPV signal response curve. Fig.12 (b) It can be seen that in the range of 1.0 to 1.0×106 In the concentration range of pM, the DPV peak current signal is linearly correlated with the logarithmic value of HBV-DNA concentration, and the regression equation is ΔI = 0.769 + 2.821lgC HBV-DNA (pM), correlation coefficient (R 2 ) is 0.998; the detection limit is based on the formula LOD=3σ / S=0.503pM (σ is the current value obtained from 11 blank experiments, S is the slope of the linear regression equation).
[0097] In order to explore the selectivity of the detection system, interference experiments were performed using HBV-2M (2 base mismatches), HBV-4M (4 base mismatches), human immunodeficiency virus (HIV), hepatitis C virus (HCV), and human papillomavirus (HPV) DNA. Fig.12 (c) As shown. The recognition region of padlock DNA hardly recognizes HBV-4M, HIV, HCV and HPV, and cannot activate the RCA reaction; however, it has a probability of recognizing HBV-2M. This is because exonuclease III does not have a cleavage effect on the 3' end of double-stranded DNA with more than 4 bases protruding or unpaired bases, but has a probability of activating the cleavage effect on the protruding or unpaired bases with less than 4 bases. Fig.12 (d) shows a parallel experiment of detecting 100nM HBV DNA using 10 different electrodes. The DPV signals obtained by the 10 different electrodes do not vary much, which reflects the excellent repeatability of the detection system.
[0098] 3.7 Testing of actual blood samples
[0099] The constructed electrochemical biosensor system was investigated for detecting HBV-DNA in human serum samples using the standard sample addition-recovery method to evaluate its applicability in actual sample detection. The pretreated human serum samples were diluted 50 times with 10mM Tris-HCl buffer (pH=7.4), and different concentrations of HBV-DNA (5pM, 100pM and 1000pM) were added to the diluted human serum samples. As shown in Table 2, the recovery values of HBV-DNA were in the range of 90.3% to 104.6%, and the relative standard deviation was in the range of 2.1% to 7.3%. HBV-DNA was not present in healthy human serum samples or the concentration of HBV-DNA was very low, so after dilution, no HBV-DNA was detected. The results show that the constructed detection system has a reasonable error range and excellent specificity, and can be applied to the detection of actual samples.
[0100] Table 2 HBV-DNA recovery test results in actual serum samples of three volunteers
[0101]
[0102]
[0103] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A probe for detecting HBV-DNA, characterized in that: It is a padlock probe, which includes an RCA circular template region and an HBV-DNA recognition region. The nucleotide sequence of the padlock probe is shown in SEQ ID NO:1, and the nucleotide sequence of HBV-DNA is shown in SEQ ID NO:
2.
2. A method for preparing a working electrode for detecting HBV-DNA using the probe as claimed in claim 1, characterized in that: The following steps are involved: The padlock probe DNA was incubated with HBV-DNA; then exonuclease III was added for incubation, followed by heat inactivation; PolyT-primer and Escherichia coli DNA ligase were added, mixed, incubated, and heat inactivated; then dNTPs and phi29 DNA polymerase without dATP were added, incubated, and heat inactivated; after the incubated sample solution was cooled, it was incubated with MB@ZIF-90, and then the supernatant was collected by centrifugation and transferred to the functionalized electrode modified with MX / MWCNTs, incubated, and then the MB not adsorbed on the electrode was washed off to obtain a working electrode.
3. Use of the working electrode prepared as claimed in claim 2 in detecting HBV-DNA.
4. A three-electrode system for detecting HBV-DNA, characterized in that: It comprises a working electrode, a counter electrode and a reference electrode, wherein the working electrode is the working electrode prepared according to claim 2, the counter electrode is a platinum wire electrode, and the reference electrode is Ag / AgCl.
5. A method for detecting HBV-DNA using the probe as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Incubate the padlock probe DNA with different concentrations of HBV-DNA respectively; then add exonuclease III for incubation, and then heat inactivate; then add PolyT-primer and Escherichia coli DNA ligase, mix, incubate, and then heat inactivate; then add dNTP and phi29 DNA polymerase without dATP, incubate, and then heat inactivate; after the incubation sample solution is cooled, incubate with MB@ZIF-90, then collect the supernatant by centrifugation, and transfer the supernatant to the functionalized electrode modified with MX / MWCNTs, incubate, then rinse off the MB not adsorbed on the electrode, and test it as a working electrode in a three-electrode system; Step 2: Electrochemical measurement was performed using a three-electrode system to obtain the DPV signal response curve of the byproduct sample solution after the RCA reaction activated by HBV-DNA with different concentrations and the supernatant released by the reaction of MB@ZIF-90 on the working electrode, and the current peak of the DPV signal response curve was linearly fitted to obtain the linear correlation between the DPV peak current signal and the logarithmic value of the HBV-DNA concentration. The regression equation was ΔI = 0.769 + 2.821lgC HBV-DNA , the correlation coefficient is 0.998; Step 3: Obtain a working electrode formed by HBV-DNA of unknown concentration according to the method in step 1, and then use a three-electrode system to perform electrochemical measurement to obtain the DPV peak current signal, and substitute it into the regression equation to obtain the logarithm of the HBV-DNA concentration, and then calculate the HBV-DNA concentration.
6. The method for detecting HBV-DNA according to claim 5, characterized in that: The preparation method of MB@ZIF-90 comprises the following steps: 43.9 mg of zinc acetate and 13 mg of MB were mixed in 4 mL of N,N-dimethylformamide and stirred at room temperature for 10 min. Then, 6 mL of DMF containing 38 mg of 2-methylimidazole aldehyde was added. The mixture was kept at room temperature for 30 min and centrifuged at 10,000 rpm for 15 min. The precipitate was repeatedly washed with methanol until the supernatant was colorless and then washed three times with ultrapure water to obtain / MB@ZIF-90.
7. The method for detecting HBV-DNA according to claim 5, characterized in that: The method for preparing the functionalized electrode modified with MX / MWCNTs comprises the following steps: Step 1), adding the MWCNTs dispersion dropwise into the MXene dispersion, oscillating and mixing continuously, then adding 24% by volume of anhydrous ethanol and 5% by volume of Nafion and oscillating and mixing to obtain a 2-7 mg / mL MX / MWCNTs dispersion; wherein the MXene content is 0.1-3.5 mg / mL, and the MWCNTs content is 0.1-3.5 mg / mL; Step 2), drop the MX / MWCNTs dispersion on the glassy carbon electrode and dry it to obtain a functionalized electrode modified with MX / MWCNTs.
8. The method for detecting HBV-DNA according to claim 7, characterized in that: The preparation method of the MXene comprises the following steps: 1 g Ti3AlC2 powder was slowly added to a mixed acid of 1.6 g LiF and 20 mL 9 M HCl, and the mixture was reacted in a water bath at 40 ° C for 48 h. The precipitate after the reaction was washed three times by centrifugation with 2 M HCl as a detergent to remove LiF in the precipitate. The precipitate was then washed with ultrapure water until the upper centrifugal liquid turned black and the lower precipitate became viscous and swollen. The centrifugal liquid was no longer replaced, and the centrifugation cycle was shaken and centrifuged three times again. The obtained black suspension was ultrasonically treated at 16 ° C for 2 h under N2 protection, and then the unetched precipitate was separated by centrifugation. The upper black liquid was Ti3C2T x MXene.
9. The method for detecting HBV-DNA according to claim 7, characterized in that: In the step 1, exonuclease III is added and incubated at 37°C for 45 minutes; PolyT-primer and Escherichia coli DNA ligase are added, mixed, and incubated at 16°C for 45 minutes; dNTPs without dATP and phi29 DNA polymerase are added, and incubated at 30°C for 2 hours; 1 mg / mL MB@ZIF-90 is used for incubation at below 25°C for 5 minutes; the supernatant is transferred to the functionalized electrode modified with MX / MWCNTs and incubated at 45°C for 40 minutes; In the step 1), a 4 mg / mL MX / MWCNTs dispersion is obtained, wherein the MXene content is 2.7 mg / mL and the MWCNTs content is 1.3 mg / mL.
10. Use of the probe as claimed in claim 1 in detecting HBV-DNA.